The inﬂuence of the design of the assessment method on the attributes of reactive backwards stepping in young adults - Chockalingam Muthukumar, Radhika; Ramachandran, Sivakumar; Vaidhyanathan, Jayashree (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Reactive backwards stepping occurs to prevent a backwards fall when a person’s centre of mass is shifted pos-teriorly by an unexpected external force. Methods such as the Balance Evaluation Systems Test (BESTest) and platform trans-lations are used to assess the ability to perform backwards stepping. However, the response may vary based on the perturba-tions administered during testing, which could reﬂect the individual’s optimal response capability. This study aims to analyse the characteristics of backwards reactive stepping in both the BESTest and moving platform methods.Methods. In this observational study, 60 healthy young adults were tested for backwards stepping using the BESTest and a moving platform. Three trials were video-recorded and analysed. The ﬁrst step length, ﬁrst step time, balance recovery length and balance recovery time were measured and compared between the BESTest and moving platform methods. Mann–Whitney U was used to test the diﬀerences at a signiﬁcance level of p < 0.05.Results. The results showed that the values for ﬁrst step length, balance recovery length and balance recovery time were smaller for the moving platform perturbation compared to the BESTest (p < 0.05). Conversely, no diﬀerence was observed in ﬁrst step time between the two methods.Conclusions. The design of the evaluation method inﬂuenced the characteristics of stepping. The moving platform elicited a more proﬁcient backwards stepping reaction compared to the BESTest.
Keywords: postural control; stepping; Balance Evaluation Systems Test; surface translation